2021
DOI: 10.1111/let.12420
|View full text |Cite
|
Sign up to set email alerts
|

The influence of volcanic activity and trophic state on plant taphonomic processes in Triassic lacustrine-deltaic systems of western Gondwana

Abstract: The impact of volcanic activity and trophic state on the preservation of plant remains from two Triassic palaeolake deposits in western Gondwana is investigated. Six taphonomic modes are identified for the Potrerillos–Cacheuta sequence and the Los Rastros Formation, along with proposed taphonomic pathways for each mode. The taphonomic pathways were compared with those proposed for the Agua de la Zorra Formation, a coeval lacustrine‐deltaic succession. In all three cases, plant preservation in off‐shore lacustr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
(133 reference statements)
0
6
0
Order By: Relevance
“…In the Cachetua palaeolake analyzed in this study, an episodic input of pyroclastic material occurred as indicated by the various tuff levels in the studied section (Salduondo et al, 2020(Salduondo et al, , 2022. The input of this material influenced diagenetic processes (Salduondo et al, 2020(Salduondo et al, , 2022 as well as primary productivity in the water column (Pedernera et al, 2021a) and thus the variability of the palynofacies composition. Therefore, the documented vertical and lateral palynofacies changes not only reflect the local depositional setting but also the influence of volcanic activity on the nutrient supply to the water column.…”
Section: Petrographic Comparison With the Potrerillos -Cacheuta Syste...mentioning
confidence: 82%
See 1 more Smart Citation
“…In the Cachetua palaeolake analyzed in this study, an episodic input of pyroclastic material occurred as indicated by the various tuff levels in the studied section (Salduondo et al, 2020(Salduondo et al, , 2022. The input of this material influenced diagenetic processes (Salduondo et al, 2020(Salduondo et al, , 2022 as well as primary productivity in the water column (Pedernera et al, 2021a) and thus the variability of the palynofacies composition. Therefore, the documented vertical and lateral palynofacies changes not only reflect the local depositional setting but also the influence of volcanic activity on the nutrient supply to the water column.…”
Section: Petrographic Comparison With the Potrerillos -Cacheuta Syste...mentioning
confidence: 82%
“…At a regional scale, the evolution of palaeolakes in the Cuyo Basin was controlled by tectonic and climatic factors but the lakes were also influenced by variable volcanic activity (Barredo, 2012;Teixeira et al, 2018). Thus the Agua de la Zorra palaeolake was located near to volcanic centres, and was therefore characterized by the episodic incursion of lava flows into the aquatic environment which affected the biotic diversity (Pedernera et al, 2021a). An input of volcanic ash falling into a lake may have positive or negative effects on the primary productivity of aquatic organisms (such as Botryococcus) which are sensitive to chemical changes in the water column (Li et al, 2021).…”
Section: Petrographic Comparison With the Potrerillos -Cacheuta Syste...mentioning
confidence: 99%
“…The successions of these basins are entirely continental and mainly include alluvial fan, river, and lake deposits. In addition, they are widely known for the good conservation of their fauna and floristic associations (Spalletti et al, 1999;Marsicano et al, 2001;Zamuner et al, 2001;Lutz et al, 2011;Mancuso et al, 2014;Ezcurra et al, 2017;Lara et al, 2017;Pedernera et al, 2021).…”
Section: Geological Settingmentioning
confidence: 99%
“…The moderate degree of breakage also could indicate a much shorter transport time and distance (Ferguson, 1985;Spicer & Parrish, 1986;Spicer, 1991). Lack of preferential orientation evidence and its arrangement consistent with stratification plans suggest that these materials would have remained floating, until deposition by settling (Pedernera et al, 2021).…”
Section: Taphonomic Remarksmentioning
confidence: 99%
“…The lava flows cause alteration of the limnological parameters, both physical (e.g., temperature and habitat reduction) and chemical (e.g., pH and salinity). The entry of volcanic ash into aquatic ecosystems also produces alterations in limnological parameters (e.g., increase in turbidity, changes in pH, conductivity, variations in nutrient concentration), which directly affect the surrounding biota from a basal trophic level (e.g., decrease in primary productivity due to modification of the microbial community) and thus modify the trophic state (Barker et al, 2000;Okorafor, 2011;Massaferro et al, 2018;Pedernera et al, 2021). Despite the evident adverse effects of volcanic activity on the surrounding ecosystems, the fossil record in lake deposits could be favored by the action of volcanism (Beherensmeyer and Hook, 1992;Pan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%